ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - Irza Shara Hervina, 12.05.52.0233; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This study aimed to examine and analyze the effect of leverage, profitability, company size, stock ownership, media exposure, the Board of Commissioners, and the solvability of the social responsibility disclosure. The population in this research was manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. A sample of 79 companies. The type of data used was secondary data. The analysis used was multiple linear regression analysis. The results showed that the variable leverage and solvability is not significant positive effect on the disclosure of social responsibility. media exposure negatively affect the social responsibility disclosure. Profitability, company size, stock ownership, and the board of commissioners significant positive effect on the disclosure of corporate social responsibility.Keywords: Leverage, Profitability, Company Size, Stock Ownership, Media Exposure, The Board Of Commissioners, Solvability, Corporate Social Responsibility